Juvenile Criminal Law in Bosnia and Herzegovina With Reference to the Criminal Legal Position and Responsibility of Juveniles (Kriminalističke teme, 2020)
Reason (s) for writing and research problem (s): The topicality of juvenile criminal law in Bosnia and Herzegovina, but also in the region, with special reference to the specific criminal law position of juveniles.Aims of the paper (scientific and/or social): Analysis of legal provisions related to the specific criminal position of minors as perpetrators of criminal offenses, including current and crucial issues related to the protective responsibility of minors.Methodology/Design: In this paper, appropriate methods were used to achieve the goal.Research/paper limitations: Do not exist.Results/ Findings: With the adoption and entry into force of the Law on Protection and Treatment of Children and Juveniles in Criminal Proceedings at the Entity and Brčko District, legal provisions relating to the criminal status of juveniles have been singled out, which is an extremely significant progress. and autonomy, although these provisions relating to state-level minors are still contained in the general part of the law.General conclusion: The tendency to humanize the criminal criminal law in Bosnia and Herzegovina justifiably requires the acceptance and adoption of international standards relating to the specific criminal status of minors and adequate protective attitude in the actions of entities or law enforcement agencies.Research/paper validity: Protective and humane treatment of juveniles is imposed as an imperative in juvenile justice.